Nuclear magnetic resonance analysis of ascorbic acid assisted lignocellulose decomposition in dilute acid pretreatment and its stimulation on enzymatic hydrolysis. (January 2022) - Sheng, Yequan; Xu, Yong
Graphical abstract: Highlights: Decomposed lignins and residual lignins showed different structural modification. Ascorbic acid blocked lignin repolymerization during pretreatment. Higher ascorbic acid concentration increased contents of decomposed lignins. Enhancement of ascorbic acid addition on enzymatic hydrolysis was dose dependent. The advantage of ascorbic acid addition worked better in higher enzyme loading. Abstract: The effect of ascorbic acid addition on lignin decomposition in the dilute acid pretreatment and the corresponding cellulose conversion of pretreated biomass have been studied. This enhancement by ascorbic acid addition was dose dependent. Decomposed and residual bulk lignins from pretreated poplar were analyzed by 2D HSQC and 31 P NMR spectra. The promotional effect on lignocellulose decomposition with the assistance of ascorbic acid addition was supported by the NMR analysis. The analysis showed that the addition of ascorbic acid has a more significant stimulation on decomposed lignins compared to residual bulk lignins. The stimulatory effect of ascorbic acid in lignocellulose decomposition benefits the cellulose conversion of the corresponding pretreated materials. Poplar pretreatment assisted with ascorbic acid (2–8% w/w) increased the final hydrolysis yield by 7.5%–32.2%. This promotional effect of ascorbic acid on enzyme digestibility was more obvious with higher enzyme loading.